The contributory revolution - Giorgini, Pierre (London, UK : ISTE Ltd., 2022)
This book sheds light on a crucial debate on the possible role of the technosciences in meeting the challenges of the future. It shows that the current contributory revolution is global and profound, and that it concerns the whole epistemological field - from the sciences to social organizations. By delving into the epistemological dimension of the lightning transition we are currently experiencing, The Contributory Revolution identifies the levers of the salutary acceleration of collective learning, now essential, but not before the debate on a possible future has been settled via the headlong rush of the technoscientist. However, after this call to move from exo-distributive technoscience, carried by deterministic and Newtonian models, to more biological and endocontributory models - or even from the arrogance of mastery to the humility of influence and alliance - it will be necessary to set its limits to avoid entering into an eco-philosophical radicalism. Only extreme humility, carried by strong spirituality, can protect us from it.
Front Matter -- The Major Dualities in How Things are Perceived -- Science and Sense, Places and Links -- Contributory Metamorphosis in the Conception of Systems and the Sciences -- The Contributory Metamorphosis of Technical Progress -- The Salutary Crisis of Joy -- Conclusion: The Limits of the Thesis -- Postface -- Appendix: Scientific and Philosophical Comments -- References -- Index -- Other titles from iSTE in Innovation, Entrepreneurship and Management
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed October 15, 2021).
John Wiley and Sons
Keywords: Technological innovations; Entrepreneurship; Entrepreneurship; Innovations; Entrepreneuriat; entrepreneurs; Entrepreneurship; Technological innovations